The Effect of Using Minecraft: Education Edition on Students' Conceptual Understanding and Collaboration - Darmawan, Chandra; Ervandi, Akhmad Joice; Muhajir; Hatip, Ahmad; Sucipto; L Tobing, Victor Maruli Tua (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
This study examines the effect of Minecraft: Education Edition on students' conceptual understanding and collaboration in Social and Natural Sciences (IPAS) learning. A quasi-experimental design with a pretest-posttest control group was used, involving 48 sixth-grade students from SDN Srambah. The sample was divided into an experimental group (Class VI A, 24 students) using Minecraft: Education Edition, and a control group (Class VI B, 24 students) receiving conventional instruction, selected through purposive sampling. Instruments included a conceptual understanding test and a collaboration questionnaire. Descriptive statistics showed a greater increase in the experimental group’s scores. Data met assumptions for parametric testing based on normality and homogeneity tests. MANOVA results indicated a significant effect of learning media on both outcomes (p < 0.001). Further tests of Between-Subjects Effects revealed that the learning method accounted for 91.9% of the variance in conceptual understanding and 94.8% in collaboration. These results suggest that Minecraft: Education Edition is more effective than traditional methods in enhancing both cognitive and collaborative skills. The findings support constructivist learning theory, highlighting the benefits of interactive, student-centered environments in fostering active engagement and meaningful learning.